1968
DOI: 10.1104/pp.43.5.811
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling of Respiration-Linked Contraction in Corn Mitochondria

Abstract: Abstract. Respiration-linked contraction of corn mitochondria is not noticeably reduced by low, uncoupling concentr*tions of dinitrophenol. However, if a oontraction/respiration ratio is calculated, the contraction proves to be uncoupled. Previous statements that contraction cannot be uncoupled from respiration are in error.The uncoupling of c-ontraction is oonsistent with the concept that dinitrophenol attacks a primary non.phosphoryla-ted high energy intermediate (I,.X). It is proposed thot this intermediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

1970
1970
1979
1979

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 16 publications
2
11
0
Order By: Relevance
“…the magnitude of the contraction under these conditions closely paralleled Ca deposition within the mitochondria. Thus, the studies of Hanson et al (10) actually parallel those of Ca2, uptake presented in Figure 5 which indeed show a dramatic reduction of Ca2+ uptake in the presence of DNP. If the site of DNP inhibition is associated with the dissipation of I X, then it seems unlikely that the pumping of K+, which results in contraction, in a KCI medium is involved directly with I~X.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…the magnitude of the contraction under these conditions closely paralleled Ca deposition within the mitochondria. Thus, the studies of Hanson et al (10) actually parallel those of Ca2, uptake presented in Figure 5 which indeed show a dramatic reduction of Ca2+ uptake in the presence of DNP. If the site of DNP inhibition is associated with the dissipation of I X, then it seems unlikely that the pumping of K+, which results in contraction, in a KCI medium is involved directly with I~X.…”
Section: Discussionsupporting
confidence: 69%
“…This is somewhat surprising since DNP has been reported to reduce the contraction of isolated corn mitochondria in KCI (10). However, in the previous experiments of Hanson et al (10), the reaction media contained phosphate and Ca2 .…”
Section: Discussionmentioning
confidence: 88%
“…The buffer employed in the isolation of plant mitochondria is either phosphate (39)(40)(41)45), or tris-HCl (25,26,33,34,36), or both (17,22,31,32). Recently, Drury et al (14)(15)(16) Plant Physiol.…”
Section: Discussionmentioning
confidence: 99%
“…27,40), cysteine is often added to the grinding medium (5, 6, 13-16, 24-26, 28-30, 33-36, 40, 41). Several workers, on the other hand, do not employ cysteine in their isolation media atall (17,22,31,32,39,45). In our experiments with mung bean mitochondria to clarify this discrepancy in theliterature, we found that the deletion of cysteine from the grinding medium altogether did not damage the mitochondrial activity (unpublished results).…”
Section: Discussionmentioning
confidence: 99%
“…ATP synthesis was sensitive to the electron transport inhibitor KCN, the uncoupler carbonyl cyanide m-chlorophenylhydrazone, and the coupling factor inhibitor oligomychr. Experi Studies from several laboratories have shown that oxidative phosphorylation in plant mitochondria is similar in many respects to that in animal mitochondria (12,13,15). While intact plant and animal mitochondria have been well characterized, they are not ideal systems for studying the mechanism or the control of oxidative phosphorylation.…”
Section: Introductionmentioning
confidence: 99%